Dialog in the echo chamber: Fake news framing predicts emotion, argumentation and dialogic social knowledge building in subsequent online discussions. (March 2023) - Scheibenzuber, Christian; Neagu, Laurentiu-Marian; Ruseti, Stefan; Artmann, Benedikt; Bartsch, Carolin; Kubik, Montgomery; Dascalu, Mihai; Trausan-Matu, Stefan; Nistor, Nicolae
Abstract: Disinformation currently floods the Internet worldwide and likely affects social knowledge building in online communities. Strategic framing in the form of emotional, value, and semantic framing is a common tool fake news producers use to more efficiently disseminate their content, yet these strategies have not been sufficiently examined, even less in relationship with the online dialog initiated by misinformation. In this exploratory study we aim to investigate the most relevant types of strategic framing and their role as predictors of news consumers' emotions, argumentation, and social knowledge building in the online dialog on a German alternative news site. Employing both manual and automated content analysis, we found significant relationships between framing in posted news articles and the subsequent online dialog. News framing predicted negative emotions in the online discussions and interfered with argumentation and social knowledge building. Conclusions pertain to digital information literacy interventions and further research on news framing. Highlights: This study combines framing theory and dialogism with disinformation content. We utilized both manual and automatic content analysis to discover prominent frames in fake news content. We analyzed roughly 1500 comments from a German fake news site. Framing predicted social knowledge building in the sense of dialogism and might have led to an echo chamber environment.